Human astrocytes develop physiological morphology and remain quiescent in a novel 3D matrix. (February 2015) - Placone, Amanda L.; McGuiggan, Patricia M.; Bergles, Dwight E.; Guerrero-Cazares, Hugo; Quiñones-Hinojosa, Alfredo; Searson, Peter C.
Abstract: Astrocytes are the most abundant glial cells in the brain and are responsible for diverse functions, from modulating synapse function to regulating the blood–brain barrier. In vivo, these cells exhibit a star-shaped morphology with multiple radial processes that contact synapses and completely surround brain capillaries. In response to trauma or CNS disease, astrocytes become activated, a state associated with profound changes in gene expression, including upregulation of intermediate filament proteins, such as glial fibrillary acidic protein (GFAP). The inability to recapitulate the complex structure of astrocytes and maintain their quiescent state in vitro is a major roadblock to further developments in tissue engineering and regenerative medicine. Here, we characterize astrocyte morphology and activation in various hydrogels to assess the feasibility of developing a matrix that mimics key aspects of the native microenvironment. We show that astrocytes seeded in optimized matrix composed of collagen, hyaluronic acid, and matrigel exhibit a star-shaped morphology with radial processes and do not upregulate GFAP expression, hallmarks of quiescent astrocytes in the brain. In these optimized gels, collagen I provides structural support, HA mimics the brain extracellular matrix, and matrigel provides endothelial cell compatibility and was found to minimize GFAP upregulation. This defined 3D microenvironment for maintaining human astrocytes in vitro provides new opportunities for developing improved models of the blood–brain barrier and studying their response to stress signals.